Evaluating the geomagnetic response to the May 2024 super storm – observations and interpretations - Ngwira, Chigomezyo M.; Nishimura, Yukitoshi; Weygand, James M.; Landwer, Lois J.; Bush, Daniel C.; Foster, John C.; Erickson, Philip J. (Frontiers in Astronomy and Space Sciences, 2025)
On 10 May 2024, a series of coronal mass ejections were detected at Earth followed by one of the most powerful geomagnetic storms since November 2003. Leveraging a multi–technique approach, this paper provides an account of the ground geomagnetic response during the 10–11 May 2024 extreme geomagnetic storm. More specifically, we show that at the mid-latitudes in the American sector, the storm produced extreme ground geomagnetic field perturbations between 01:50 UT and 02:30 UT on 11 May. Then using the Spherical Elementary Current System method, it is shown that the perturbations were associated with an intense westward propagating auroral westward electrojet current. Finally, with the aid of auroral all-sky images from the Missouri Skies Observatory, we demonstrate that an intense isolated substorm event with onset located between the Great Lakes region and the East Coast United States was the main source of the extreme westward electrojet current and the geomagnetic field perturbations at these typical mid-latitude locations. This study emphasizes the increased risk associated with expansion of the auroral oval into the mid-latitudes during extreme geomagnetic activity.